Electrochemical Behavior of Paraquat on a Highly Ordered Biosensor Based on an Unmodified DNA-3D Gold Nanoparticle Composite and Its Application. (20th January 2015) - Niu, Ling Mei; Liu, Fei; Wang, Wei; Lian, Kao Qi; Ma, Li; Shi, Hong Mei; Kang, Wei Jun
Graphical abstract: Highlights: Construction of unmodified DNA-3D gold nanoparticle composite was investigated. Fabrication of hairpin DNA on GNPs was studied. Redox mechanism of paraquat on the modified electrode was elucidated. Determination method of paraquat on the modified electrode was established. Abstract: DNA usually adsorbs gold nanoparticle by virtue of mercapto or amino group at one end of a DNA molecule. However, in this study, we report a highly ordered biosensor constructed using unmodified DNA molecules with consecutive adenines and three-dimensional gold nanoparticles (3D GNPs). The unmodified DNA-3D GNP composite was fabricated on gold electrodes and characterized through the use of scanning electron microscopy (SEM), atomic force microscopy (AFM), and electrochemical methods. Using an electrochemical quartz crystal microbalance (EQCM), the mechanism by which the unmodified DNA and GNPs combined was also studied. The modified electrode exhibited an ultrasensitive response to paraquat. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to study the linear relationships between the concentrations and the reduction peak currents. The linear relationship for DPV is 7.0 × 10 −9 M to 1.5 × 10 −6 M with a detection limit of 2.0 × 10 −10 M. The redox mechanism of paraquat on this modified electrode was also elucidated. The feasibility of the proposed assay for use in human serum, human urine, and natural samples was investigated, and satisfactory results were obtained.